2012
DOI: 10.3171/2012.1.jns111013
|View full text |Cite
|
Sign up to set email alerts
|

The branching pattern of the middle cerebral artery: is the intermediate trunk real or not? An anatomical study correlating with simple angiography

Abstract: Interrelations of these vascular structures and their influences on the cortical branches originating from them are clinically important. The information presented in this study will ensure reliable diagnostic approaches and safer surgical interventions, particularly with MCA selective angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
3
26
2
1
Order By: Relevance
“…This observation is underlined by previous microsurgical studies which demonstrated a higher frequency of dominant inferior trunks compared with superior trunks 15 16. However, our rate is higher than the aforementioned studies, which found inferior trunks to be dominant in up to 54% 15. This can be explained by the fact that our study design only allowed the classification of trunks as dominant and non-dominant, even in cases where differentiation of vessel caliber was difficult.…”
Section: Discussioncontrasting
confidence: 70%
“…This observation is underlined by previous microsurgical studies which demonstrated a higher frequency of dominant inferior trunks compared with superior trunks 15 16. However, our rate is higher than the aforementioned studies, which found inferior trunks to be dominant in up to 54% 15. This can be explained by the fact that our study design only allowed the classification of trunks as dominant and non-dominant, even in cases where differentiation of vessel caliber was difficult.…”
Section: Discussioncontrasting
confidence: 70%
“…After this date, some important progress was achieved in parallel with hardware and software advancement in computer technology as well as image processing technology in neurological radiology. according to literature records, it may be concluded that cadaveric and CT angiographic measurements are similar and overlap with each other (3,6). This may provide considerable intraoperative safety in surgical approaches related to anatomical structures such as OphA.…”
Section: █ Discussionmentioning
confidence: 88%
“…If the intermediate trunk cannot be selected, the operator should aim for the selection of a branch of the inferior division. It has been reported that the inferior division is most commonly the dominant division counting with the largest diameter [8]. …”
Section: Discussionmentioning
confidence: 99%
“…The precentral, central and postcentral (also known as the anterior parietal) arteries usually arise from the intermediate trunk. These branches give the blood supply to the primary somatosensory cortex [8]. …”
Section: Methodsmentioning
confidence: 99%